Tihu Beach Tourism Development Strategy in Bone Bolango District - Erlansyah, Erlansyah; Antu, Yulinda R; Anwar, Rustam (Gorontalo State University, 2021)
Tihu Village is one of the villages located in the coastal area of Tomini Bay. Administratively, this village is included in the Bonepantai District, Bone Bolango Regency, Gorontalo Province. This bay has the potential of coastal and marine resources, especially fishery resources. This potential can certainly be used to improve the welfare or economy of the community in the present and in the future. The purpose of this research is to formulate a strategy for developing Tihu beach tourism. The analysis to determine the strategy of developing Tihu beach tourism uses 2 (two) data analyzes, namely descriptive analysis, and AHP (Analytical Hierarchy Process). Based on the results of the study, the main priority is the socio-cultural factor with a value of 0.426, the second priority is the economic factor with a value of 0.414, the third priority is the accommodation factor with a value of 0.110, and the last priority is the safety factor with a value of 0.056.